Current practices of high and low flow oxygen therapy and humidification in UK neonatal units. (29th September 2015) - Nath, P; Ponnusamy, V; Willis, K; Bisset, L; Clarke, P
Abstract : Background: Oxygen therapy delivered via infranasal cannulae is widely used to support breathing in term and preterm neonates. High-flow (HF) nasal therapy delivers heated, humidified and blended oxygen/air via small calibre nasal cannulae at flow rates of >1 L/min. Cold, non-humidified gases delivered at HF rates may lead to significant dysfunction of the nasopharynx through drying and damage to the nasal mucosa, potentially predisposing to staphylococcal infection. Proper humidification is associated with lower post-extubation failure rates and fewer local complications. Aim: To examine current practices of humidification of HF and low-flow (LF) nasal oxygen therapy in UK neonatal units. Methods: Telephone questionnaire survey of all 214 UK neonatal units (July 2009–Oct 2009) asking the senior nurse about their unit's practice for humidification and delivery of HF and LF oxygen. Results: The authors obtained responses from 202/214 (94%) units. Data are summarised by country (table 1 ) and designation level (table 2 ) of neonatal units. Conclusion: Wide variations exist in use of HF and LF oxygen therapy and humidification. Most units humidify HF oxygen, but fewer than half of units humidify LF oxygen. Future studies are needed to compare the incidence of nasopharyngeal staphylococcal colonisation/infection, and the duration of oxygen supplementation in infants receiving humidified vs non-humidified HF and LF oxygen therapies.